Islamic Economic Thought Has Existed Since The Time Of The Prophet Adam Alaihis Salam - Luluk Latifah; Isma Swadjaja; Dian Berkah; Muridah Isnawati; Warsidi Warsidi (Jurnal Ilmiah Ekonomi Islam, 2023)
Studies on the history of Islamic economics are still very rare, especially the study of Islamic economics before the Nubuwah period or the time of the appointment of the Prophet Muhammad as a Prophet and Apostle. The purpose of this study is to prove that Islamic economic civilization has existed since the time of the Prophet Adam sent by Allah to the earth. The method used in this study is a qualitative method with a research library, with a historical methodology approach. The results of the study said that Islamic economic civilization existed long before the Nubuwah era or the time of the appointment of the Prophet Muhammad SAW as a prophet and apostle. At the time of the Prophet Adam, there were very simple economic activities to meet their basic or primary needs. These economic activities are consumption, distribution and production. More and more economic functions were practiced during the time of Noah and Yunus, including the functions of transportation and trade. Even at the time of the Prophet Yusuf, there was already a supply and warehousing function. The time when Prophet Musa carried out economic activities more fully and in detail, namely when Prophet Musa a.s. met with two girls who were queuing to get their cattle to drink and then Prophet Musa offered himself as a representative (wakalah contract) to carry out the duties of the two girls. Furthermore, more intense cooperation in the field of livestock maintenance and development as employees (managers) and shahibul Maal (livestock owners). The economic functions at the time of the Prophet Muhammad were more complete, namely the functions of production, consumption, distribution, human resources and investment. Almost everything was lived by the Prophet Muhammad himself since the age of 8 years. The initial journey that the Prophet Muhammad had carried out was as a deputy at the beginning as a shepherd with a salary system, then as a mudharib in a trading business when the prophet Muhammad was not married, and then after marrying Khadijah the Prophet acted as a shahibul mall and at the same time an investor and this is when the Prophet Muhammad have a lot of time to think about the condition of society, at this time the Prophet had achieved financial freedom or freedom of money